Management of Vasoproliferative Tumors of the Retina with Macular Complications by Pars Plana Vitrectomy Combined with Episcleral Cryotherapy. (13th April 2021) - Zhang, Wenhua; Qiang, Zeyuan; Song, Hao; Li, Xiaoli; Dan, Handong; Ge, Keke; Li, Pan; Huang, Zixu; Wang, Dongdong; Chen, Feng; Zheng, Bin; Song, Zongming
Abstract : Objective . To evaluate the efficacy of pars plana vitrectomy (PPV) combined with episcleral cryotherapy in treating vasoproliferative tumors of the retina (VPTR) with macular complications. Methods . In this retrospective noncomparative interventional case-series analysis, we included 11 eyes of ten patients diagnosed with VPTR. All patients underwent comprehensive ophthalmic examinations and were treated with PPV combined with episcleral cryotherapy. Best-corrected visual acuity (BCVA), tumor activity, retinal morphological structure, and postoperative complications were evaluated. Results . Macular complications included epimacular membrane ( n  = 10), macular hole ( n  = 3), and macular edema ( n  = 1). Tumors were treated with triple freeze-thaw episcleral cryotherapy during PPV. The mean logarithm of minimal angle of resolution (logMAR) BCVA dropped from 0.62 ± 0.58 to 0.39 ± 0.46. The difference between the mean values of logMAR BCVA before and after treatment was statistically significant ( t  = 2.48, P = 0.033 ). The tumor activity was controlled effectively in nine cases. Compared with preoperative tumor activity, tumor activity after treatment was significantly lower (P < 0.01 ). The increase of central retinal thickness and the disruption of retinal layers were associated with macular holes, macular edema, and retinal proliferative membrane. After the treatment, visual acuity improved in 91% of the cases, and 73% had no long-term complications. Conclusion . PPV combined with episcleral cryotherapy promoted tumor regression, preserved retinal integrity, and improved visual acuity. Thus, the combination of PPV with episcleral cryotherapy can be considered effective and safe for the management of VPTR with macular complications.